Developing Digital Banking Products and Technologies in the Context of Economic Security of Banks: Managerial and Information-Analytical Aspects - Bondaruk, T. H.; Bondaruk, O. S. (Statistics of Ukraine, 2025)
The article reveals the impact of digital transformation on the efficiency of management of financial and operational risks, and on the resilience of the Ukrainian banking system.It is substantiated that the digital transformation of bank activities goes beyond technological change and forms a new management paradigm based on big data arrays, computerization of processes, artificial intelligence, and integrated information-analytical systems. It is demonstrated that the quality of information-analytical support is a determinant of the effective financial and operational risk management, the banks’ resilience to external and internal threats and their overall stability.The dynamics of cashless payments and payment infrastructure in Ukraine was analyzed, revealing a steady expansion of digital financial services and the growing role of mobile and contactless payment technologies. A comparative assessment and ranking of leading Ukrainian banks by digital performance was conducted by key criteria, including the functionality of mobile applications, the depth of Big Data and AI usage, the maturity of API solutions, the online document management, and the cybersecurity. The results show that banks with a higher digital performance demonstrate stronger competitive advantages, greater adaptability to market changes, improved risk management capabilities, and a higher level of economic security.It is concluded that digital bank products and technologies constitute a strategic tool for strengthening banks’ economic security, provided that they are integrated into a comprehensive system of managerial and information-analytical support. The practical significance of the research is in its applicability for improving banks’ digital strategies, enhancing risk management systems, and developing an advanced model for secure operation of the banking sector in Ukraine.